120k views
5 votes
Solve the following equation by identifying all of its roots including all real and complex numbers. In your final answer, include the necessary steps and calculations. Hint: Use your knowledge of factoring polynomials.

(x2 + 1)(x3 + 2x)(x2 - 64) = 0

1 Answer

4 votes

Answer:


{x}= \pm \: i\: or \: x = 0 \: or \: {x}= \pm √(2)i \: or \: {x}= \pm8

Explanation:

The given polynomial is


( {x}^(2) + 1)( {x}^(3) + 2x)( {x}^(2) - 64) = 0

By the zero product principle,


{x}^(2) + 1 = 0 \: or \: {x}^(3) + 2x = 0 \: or \: {x}^(2) - 64 = 0

Or


{x}^(2) + 1 = 0 \: or \: x( {x}^(2) + 2)= 0 \: or \: {x}^(2) - 64 = 0

This implies that;


{x}^(2)= - 1 \: or \: x = 0 \: or \: ( {x}^(2) + 2)= 0 \: or \: {x}^(2) = 64


{x}= \pm √( - 1) \: or \: x = 0 \: or \: {x} = \pm √( - 2) \: or \: {x}= \pm √(64)

Hence the roots are:


{x}= \pm \: i\: or \: x = 0 \: or \: {x}= \pm √(2)i \: or \: {x}= \pm8

User N P
by
5.2k points